Antagonistic effect of Cry1Ac and Cry1Jb on cotton bollworm (Helicoverpa armigera) - CHELLIAH, ANURADHA; GUPTA, GORAKH PRASAD; KARUPPIAH, SASIKUMAR; KUMAR, POLUMETLA ANANDA (The Indian Journal of Agricultural Sciences, 2012)
The interaction of two crystal proteins, Cry1Ac and Cry1Jb was evaluated against cotton bollworm (Helicoverpa armigera). The 50% lethal concentrations (LC50s) were estimated to be 2.29 ng/ml and 6 039 ng/ml for Cry1Ac and Cry1Jb, respectively. When mixtures of these toxins in different proportion were assayed, the expected LC50s were lower than the observed LC50s, indicating a clear antagonism between the two toxins. Ligand blotting showed that both the toxins bind to 110kDa APN corroborating the results. This is the first report of antagonism of Cry1Jb with Cry1Ac toxin against cotton bollworm. This trait may prove useful for combating insecticide resistance and for improving the activity of microbial insecticides.